2022
DOI: 10.3390/ijerph192013524
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Access to Kidney Transplantation in France: A Mixed Methods Research Protocol

Abstract: Kidney transplantation is the best renal replacement therapy (medically and economically) for eligible patients with end-stage kidney disease. Studies in some French regions and in other countries suggest a lower access to the kidney transplant waiting listing and also to kidney transplantation, once waitlisted, for women. Using a mixed methods approach, this study aims to precisely understand these potential sex disparities and their causes. The quantitative study will explore the geographic disparities, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…This qualitative study was part of a larger project which aimed to understand sex-based and/or gender-based disparities of access to KT in France. 19 This study and the data collection were authorized by the French National School of Public Health data protection officer. All patients and nephrologists read an information letter and gave their informed oral consent prior to the interviews.…”
Section: Methodsmentioning
confidence: 99%
“…This qualitative study was part of a larger project which aimed to understand sex-based and/or gender-based disparities of access to KT in France. 19 This study and the data collection were authorized by the French National School of Public Health data protection officer. All patients and nephrologists read an information letter and gave their informed oral consent prior to the interviews.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, qualitative and quantitative data will be collected and analyzed simultaneously. Then the results of both studies will be integrated and discussed in view of the main objective of the study (Adoli et al, 2022). The methodologies of the quantitative and qualitative studies and the strategies for integration of the results will be discussed in the next sections.…”
Section: Methodsmentioning
confidence: 99%
“…1 Introduction and the background to the study Chronic Kidney Disease (CKD) can be identified as one of the non-communicable diseases (NCDs) which affect millions of people worldwide, including in Sri Lanka and Poland, every year (Lameire et al, 2021;Adoli et al, 2022). The prevalence of CKD has been rising over the last three decades, especially among Sri Lankan farming communities, due to the identifying CKD with unknown etiology (CKDu) and the increment of NCDs such as hypertension and diabetes mellitus (Rajapakse et al, 2016;Kumaresan and Senawirathne, 2017;Kafle et al, 2019).…”
mentioning
confidence: 99%
“…Chronic Kidney Disease (CKD) represents a significant global health challenge, impacting millions of individuals worldwide, including in Sri Lanka [ 1 , 2 ]. Over the past three decades, the prevalence of CKD in Sri Lankan farming communities has notably increased, primarily due to two factors: the emergence of Chronic Kidney Disease of Unknown Aetiology (CKDu) and a rise in non‐communicable diseases such as hypertension and diabetes mellitus within the population [ 3 ].…”
Section: Introductionmentioning
confidence: 99%